Assessing hepatic impairment in Fontan‐associated liver disease using the HepQuant SHUNT test. (1st August 2019) - Lemmer, Alexander; VanWagner, Lisa; Gasanova, Zaira; Helmke, Steve; Everson, Gregory T.; Ganger, Daniel
Abstract: Background & Aims: Fontan surgery for single ventricle congenital heart disease leads to Fontan‐associated liver disease (FALD). Typical laboratory tests, imaging, and histopathology cannot predict clinical severity in FALD. HepQuant SHUNT is a proprietary serum test of hepatic function and physiology that has not yet been evaluated in FALD. Methods: Fourteen adult FALD patients at a single urban tertiary care center who underwent a Fontan procedure in childhood received HepQuant SHUNT testing between September 2015 and April 2018. The HepQuant SHUNT disease severity index (DSI) assesses global liver function and physiology from systemic and portal hepatic filtration rates (HFRs, clearances adjusted for body mass) of orally and intravenously administered cholates labeled with deuterium or 13C. The SHUNT parameter of the test measures portal systemic shunting from the ratio of Systemic HFR to Portal HFR. Chart review included laboratory tests, imaging, and clinical findings. Data from FALD patients were compared with data from healthy controls. Results: The average DSI and SHUNT values for the FALD patients were 17.5% and 36.1%, respectively, compared to 9.2% and 24.1%, respectively, for controls. Twelve (85.7%) FALD patients had a DSI >15 (upper limit of normal). Seven (50.0%) FALD patients had SHUNT values >30% (upper limit of normal), while three FALD patients (21.4%) had SHUNT values >49%. One FALD patient with preoperative SHUNT of 69%, who underwent a combined heart‐liver transplant, had confirmed cirrhotic morphology within the liver explant. Conclusions: This pilot study demonstrated that most FALD patients had hepatic impairment detected by abnormal DSI, with a smaller number having markedly elevated SHUNT values >49% suggesting intrinsic liver disease. The HepQuant SHUNT test may be useful in detecting and quantifying liver disease severity in FALD patients.